2007
DOI: 10.1021/jp067630t
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Adsorption on Modified ETS-10

Abstract: The interaction of xenon with silver ETS-10 is found to be unusually strong. Xenon adsorption was studied on Na-ETS-10 and its silver exchanged counterpart, Ag-ETS-10, by gas chromatography and gravimetric adsorption. High adsorption capacities were observed even at low pressure (6 wt % Xe at 0.5 Torr and 25 °C). High isosteric heats of adsorption for xenon on Ag-ETS-10 were observed, higher than on any other adsorbent reported to date. High selectivity of xenon over nitrogen and oxygen is also observed, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 11 publications
2
56
0
Order By: Relevance
“…The M06-L functional is used in this work since in a recent comparative study on the performance of nine different DFT functionals to calculate the interaction enthalpy of methane with a cluster model of Na-ETS-10, the M06-L approach was found to provide the best results [21].Besides,the M06-L approach together with a cluster model was found to provide very accurate energetic, vibrational and structural information for some other difficult systems such as i) adsorption of CO on MgO(001) [30], ii) the adsorption of CO and NO on Ni-doped MgO(001) [31], and iii) the interaction of water with open metal sites of CuBTC [32]. Very encouragingly, recent works concerning the interaction of CO with the (111) surfaces of Rh, Pt, Cu, Ag and Pd [33] or the interaction of benzene, pyridine, thymine and cytosine with Au(111) [34]showed that the M06-L method is suitable for treating dispersion dominated interactionsof adsorbateswith metallic surfaces [35].The M06-L approach was also effectively employed to predict reaction energies in organometallic systems [36][37][38] and the benchmark study on the interaction of hydrocarbons and smaller gases with several zeolite clusters byZhao and Truhlar [39]shows that the M06 family of functionals is well suited to study this kind of systems.Additionally, in our very recent work on the interaction of five atmospheric gases with Na-ETS-10 [21], calculated enthalpic data for methane, nitrogen and, at some extent, carbon dioxide, and calculated vibrational data for methane, nitrogen, hydrogen, carbon dioxide and water were found to be in very satisfactory agreement with experimental isosteric heats [40,41] and infrared results [42][43][44][45], respectively. The same 2Ti cluster model used in Ref.…”
Section: Computational Detailsmentioning
confidence: 58%
“…The M06-L functional is used in this work since in a recent comparative study on the performance of nine different DFT functionals to calculate the interaction enthalpy of methane with a cluster model of Na-ETS-10, the M06-L approach was found to provide the best results [21].Besides,the M06-L approach together with a cluster model was found to provide very accurate energetic, vibrational and structural information for some other difficult systems such as i) adsorption of CO on MgO(001) [30], ii) the adsorption of CO and NO on Ni-doped MgO(001) [31], and iii) the interaction of water with open metal sites of CuBTC [32]. Very encouragingly, recent works concerning the interaction of CO with the (111) surfaces of Rh, Pt, Cu, Ag and Pd [33] or the interaction of benzene, pyridine, thymine and cytosine with Au(111) [34]showed that the M06-L method is suitable for treating dispersion dominated interactionsof adsorbateswith metallic surfaces [35].The M06-L approach was also effectively employed to predict reaction energies in organometallic systems [36][37][38] and the benchmark study on the interaction of hydrocarbons and smaller gases with several zeolite clusters byZhao and Truhlar [39]shows that the M06 family of functionals is well suited to study this kind of systems.Additionally, in our very recent work on the interaction of five atmospheric gases with Na-ETS-10 [21], calculated enthalpic data for methane, nitrogen and, at some extent, carbon dioxide, and calculated vibrational data for methane, nitrogen, hydrogen, carbon dioxide and water were found to be in very satisfactory agreement with experimental isosteric heats [40,41] and infrared results [42][43][44][45], respectively. The same 2Ti cluster model used in Ref.…”
Section: Computational Detailsmentioning
confidence: 58%
“…1 Silver ETS-10 has shown extraordinary promise as a xenon adsorbent. 2 Zeolite-supported silver has also been utilized in antibacterial materials, as catalysts, and as adsorbents for other noble gases [3][4][5][6][7][8][9] as well as for gaseous mercury adsorption. 10 This range of properties arises from variations in the chemical states and positions of silver species in the zeolite frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…The unusual ability of ETS-10 to induce the formation of supported surface silver nanoparticles (NPs) may correspond to its extraordinary behaviour in the adsorption of noble gases. 2 In this study, the silver species present in Ag/ETS-10 and Ag/Mor after exposing the materials to various activation conditions was investigated using electron microscopy, XRD, SEM and solid-state 109 Ag, 29 Ag/Mor samples performed differently when they were tested for mercury adsorption in a flue gas emission, implying that zeolite structure has a strong effect on formed silver species and, hence, on their applications.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39][40] Silver exchanged zeolites are exceptional adsorbents for noble gases, [41,42] while silver nanoparticles have proven antimicrobial activity, [43][44][45] and silver zeolite can be used as photocatalyst. [46,47] In addition, silver can amalgamate with mercury at elevated temperatures but, at temperatures above 227 8C, the silvermercury amalgam decomposes to release the mercury.…”
mentioning
confidence: 99%